Abnormalities of sleep in patients with the chronic fatigue syndrome. Issue 6886 (1st May 1993) - Morriss, R; Sharpe, M; Sharpley, A L; Cowen, P J; Hawton, K; Morris, J
Abstract : OBJECTIVE--To determine whether patients with the chronic fatigue syndrome have abnormalities of sleep which may contribute to daytime fatigue. DESIGN--A case-control study of the sleep of patients with the chronic fatigue syndrome and that of healthy volunteers. SETTING--An infectious disease outpatient clinic and subjects' homes. SUBJECTS--12 patients who met research criteria for the chronic fatigue syndrome but not for major depressive disorder and 12 healthy controls matched for age, sex, and weight. MAIN OUTCOME MEASURES--Subjective reports of sleep from patients' diaries and measurement of sleep patterns by polysomnography. Subjects' anxiety, depression, and functional impairment were assessed by interview. RESULTS--Patients with the chronic fatigue syndrome spent more time in bed than controls (544 min v 465 min, p < 0.001) but slept less efficiently (90% v 96%, p < 0.05) and spent more time awake after initially going to sleep (31.9 min v 16.6 min, p < 0.05). Seven patients with the chronic fatigue syndrome had a sleep disorder (four had difficulty maintaining sleep, one had difficulty getting to sleep, one had difficulty in both initiating and maintaining sleep, and one had hypersomnia) compared with none of the controls (p = 0.003). Those with sleep disorders showed greater functional impairment than the remaining five patients (score on general health survey 50.4% v 70.4%, p < 0.05), but their psychiatric scores were not significantly different. CONCLUSIONS--Most patients with the chronic fatigue syndrome had sleep disorders, which are likely to contribute to daytime fatigue. Sleep disorders may be important in the aetiology of the syndrome.